Photoactivated perylenequinone toxins in fungal pathogenesis of plants - Daub, M.E.; Herrero, S.; Chung, K-R.
Several genera of plant pathogenic fungi produce photoactivated perylenequinone toxins involved in pathogenesis of their hosts. These toxins are photosensitizers, absorbing light energy and generating reactive oxygen species that damage the membranes of the host cells. Studies with toxin-deficient mutants and on the involvement of light in symptom development have documented the importance of these toxins in successful pathogenesis of plants. This review focuses on the well studied perylenequinone toxin, cercosporin, produced by species in the genus ercospora. Significant progress has been made recently on the biosynthetic pathway of cercosporin, with the characterization of genes encoding a polyketide synthase and a major facilitator superfamily transporter, representing the first and last steps of the biosynthetic pathway, as well as important regulatory genes. In addition, the resistance of Cercospora fungi to cercosporin and to the singlet oxygen that it generates has led to the use of these fungi as models for understanding cellular resistance to photosensitizers and singlet oxygen. These studies have shown that resistance is complex, and have documented a role for transporters, transient reductive detoxification, and quenchers in cercosporin resistance.
Keywords: PLANT DISEASE; NON-SPECIFIC TOXIN; ACTIVE OXYGEN; PYRIDOXINE; ZINC CLUSTER TRANSCRIPTION FACTOR